Cardioprotective effect of lithium ascorbate in an in vivo model of myocardial infarction - E. V. Plotnikov; V. I. Chernov; A. V. Mukhomedzyanov; L. N. Maslov; M. S. Yusubov; M. S. Larkina; A. A. Artamonov; M. V. Belousov (Бюллетень сибирской медицины)
The aim of the work was to study the cardioprotective effect of lithium ascorbate in an in vivo model of myocardial infarction. In the course of the study, we searched for compounds promising for therapy of acute myocardial infarction.Materials and methods. Myocardial infarction was modeled in Wistar rats by ligating the left coronary artery (the duration of ischemia was 45 minutes) followed by ligature loosening and 120-minute reperfusion. All manipulations were performed under alpha-chloralose anesthesia with mechanical lung ventilation and recording heart rate, blood pressure, and ECG. Lithium ascorbate was administered intravenously at a dose of 100 mg / ml before ischemia. The area at risk (the ischemia / reperfusion zone) was detected by staining the myocardium with tightened ligature with 5% potassium permanganate. After that consecutive myocardial slices were prepared, and infarct size was determined. Differentiation of the infarct size from the area at risk was performed by staining with 1% 2,3,5-triphenyl tetrazolium chloride solution for 30 minutes at 37 ºC. The infarct size and the area at risk were determined by the planimetric method. The serum concentration of myocardial damage marker creatine kinase-MB (CK-MB) was measured using ELISA kits.Results. Lithium ascorbate reduced the infarct size / area at risk ratio by 38% and decreased the serum CPKMB level in the experimental animals by 42% compared to the control group. Lithium ascorbate did not affect hemodynamics parameters during coronary artery occlusion and reperfusion.Conclusion. The cardioprotective effect of lithium ascorbate in cardiac ischemia / reperfusion in vivo was found.